2003
DOI: 10.1098/rspb.2003.2383
|View full text |Cite
|
Sign up to set email alerts
|

Towards the delineation of the ancestral eutherian genome organization: comparative genome maps of human and the African elephant (Loxodonta africana) generated by chromosome painting

Abstract: This study presents a whole-genome comparison of human and a representative of the Afrotherian clade, the African elephant, generated by reciprocal Zoo-FISH. An analysis of Afrotheria genomes is of special interest, because recent DNA sequence comparisons identify them as the oldest placental mammalian clade. Complete sets of whole-chromosome specific painting probes for the African elephant and human were constructed by degenerate oligonucleotide-primed PCR amplification of flow-sorted chromosomes. Comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 58 publications
5
57
0
3
Order By: Relevance
“…In addition, the recent human : xenarthran data from Richard et al (2003b) allow us to further clarify the presumed synapomorphies uniting the Afrotheria. However, confirmation that these cytogenetic characters constitute Afrotherian synapomorphies as opposed to ancestral placental states would be strengthened by outgroup comparison to a marsupial representative which is lacking (Frönicke et al 2003;Yang et al 2003). Frönicke et al (2003) identified HSA 5/21 in the elephant, suggesting that this composite, together with HSA 1/19p, may be a synapomorphy that unites Afrotheria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the recent human : xenarthran data from Richard et al (2003b) allow us to further clarify the presumed synapomorphies uniting the Afrotheria. However, confirmation that these cytogenetic characters constitute Afrotherian synapomorphies as opposed to ancestral placental states would be strengthened by outgroup comparison to a marsupial representative which is lacking (Frönicke et al 2003;Yang et al 2003). Frönicke et al (2003) identified HSA 5/21 in the elephant, suggesting that this composite, together with HSA 1/19p, may be a synapomorphy that unites Afrotheria.…”
Section: Discussionmentioning
confidence: 99%
“…some species in several recent publications (Korstanje et al, 1999;Froenicke et al, 2003;Yang et al, 2003) indicates the presence of rearrangement hotspots at the junction of HSA4 and 8 orthologous segments. The reciprocal Zoo-FISH data identify this association as a combination of HSA4 with the p-arm of HSA8 (Fig.…”
Section: Bea4-8pmentioning
confidence: 97%
“…The differences in interpretation are primarily related to the recognition of a single large chromosome (corresponding to HSA 1) in the placental ancestor (Murphy et al, 2003), the detection of the 10q/12p/22q conserved syntenic segmental association , and fusion of HSA1/19p (Yang et al, 2003, n¼22) based on its presence in Afrotheria (aardvark, elephant, golden mole and elephant shrew), at the time regarded as the most basal split in the eutherian tree (Murphy et al, 2001a, b). The more recent studies appear, however, to have converged on n¼23 for Placentalia (that is, the eutherian ancestral karyotypes of Froenicke et al, 2003;Wienberg, 2004;Ferguson-Smith and Trifonov, 2007), and an identical n¼23 in the boreoeutherian ancestral karyotype (BAK; Froenicke, 2005;Froenicke et al, 2006;Robinson et al, 2006).…”
Section: Ancestral Placental Karyotypes and The Detection Of Synteniementioning
confidence: 99%